Do public transfers "crowd out" private charitable giving? Some econometric evidence for the Federal Republic of Germany - Karl-Heinz Paqué (Kiel Institute of World Economics (IfW); ZBW – Leibniz Information Centre for Economics, 1982)
In the last two decades, most industrialized western nations, have experienced a marked increase of government intervention in economic affairs. This peculiar historical trend is followed by a growing professional interest among economists in the impact which public expenditure and taxation may have on the level of private economic activity, the so-called crowding-out effects. While the bulk of the theoretical and empirical research in this field focuses on the macroeconcmic effects of fiscal policy on private investment behaviour, sane recent work has turned to specific allocative issues: the long-lasting controversy between Martin Feldstein and Robert Barro on the impact of social security on private saving figures as a prominent case of this new branch of research. The present paper is aimed at yielding some-new econometric evidence on specific allocative crowding-out effects. More precisely, it raises the question whether the growth of particular public expenditure items has exerted any negative (or positive) influence on the level of private charitable contributions in the Federal Republic of Germany during the last twenty years. The paper is divided into four parts: Section 2 tries to put the empirical crcwding-out analysis into sane rudimentary theoretical framework. Section 3 develops an econometric approach completely analoguous to the model used by Abrams & Schmitz in their study on charity crowding-out in the U.S. The serious shortcomings of this approach point to a more comprehensive time-series-cross-section analysis which will be presented in section 4. Apart from the evidence on crowding-out, the extended model will yield a few insights concerning seme socioeconanic determinants of private giving behaviour. Section 5 concludes the paper with a few remarks on the validity of the empirical results.
Keywords: 330